MANAGEMENT OF ANTHRACNOSE OF BANANA BY UV IRRADIATION - N. A. Bokhari; I. Siddiqui; K. Parveen. I. Siddique; H. Rizwana; D. A. W. Soliman (Journal of Animal and Plant Sciences, 2013)
Anthracnose is a postharvest disease of banana Musa acuminata Colla caused by the fungus Colletotrichum musae Berk & Curtis. The present study was carried out to manage this pathogen in vitro and in vivo using different types of ultraviolet (UV) radiations. Two in vitro bioassays were carried out. In the first bioassay, malt extract agar medium was used in 9-cm diameter Petri plates. Plates were exposed for 15, 30, 45,..,120 minutes to three types of UV radiations viz. UV-A of wavelength 365 nm, UV-B of wavelength 302 nm and UV-C of wavelength 254 nm. In the second bioassay, malt extract broth was used in 250-mL conical flasks with the same treatments of UV irradiation. UV-C radiation exhibited the highest fungicidal potential in the two in vitro bioassays. UV-C irradiation for 45 minutes and above completely inhibited the fungal growth. Different doses of UV-B radiation reduced fungal biomass and radial growth by 15–75% and 34–75% in malt extract broth and malt extract agar media over control (light), respectively. The effect of UV-A radiation was generally insignificant. In vivo bioassays were carried out by exposing C. musae inoculated banana fruits to the three types of UV radiations for two hours. UV-C irradiation completely inhibited the fungal growth.
Keywords: Anthracnose; Banana; Colletotrichum musae; UV irradiation